2003
DOI: 10.1210/en.2003-0033
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Inhibits the Development of Mouse Preimplantation Embryos in Vitro

Abstract: Although ghrelin acts as a modulator of feeding behavior and energy metabolism in the central nervous system, recent studies have implicated the peripheral actions of ghrelin in reproductive tissues. Here, we investigated the expression of ghrelin and its receptor (GHS-R) in mouse oocyte and preimplantation embryos, and we examined the role of ghrelin in the regulation of early embryo development. Both ghrelin and GHS-R mRNAs were detected in morula or more advanced embryo stages. As for the origin of ghrelin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
1
8

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 66 publications
5
104
1
8
Order By: Relevance
“…In addition, ghrelin levels in uterine fluid have been proven to dramatically increase during fasting in mice, and ghrelin has been recently reported to inhibit the development of mouse preimplantation embryos in vitro (Kawamura et al 2003). In good agreement, we have recently observed that chronic ghrelin treatment during the first half of pregnancy in the rat induced a significant reduction in the litter size (Fernandez-Fernandez et al 2005).…”
Section: Rodent Datamentioning
confidence: 58%
“…In addition, ghrelin levels in uterine fluid have been proven to dramatically increase during fasting in mice, and ghrelin has been recently reported to inhibit the development of mouse preimplantation embryos in vitro (Kawamura et al 2003). In good agreement, we have recently observed that chronic ghrelin treatment during the first half of pregnancy in the rat induced a significant reduction in the litter size (Fernandez-Fernandez et al 2005).…”
Section: Rodent Datamentioning
confidence: 58%
“…Ghrelin also negatively regulates cell viability and proliferation (Cassoni et al, 2000;Cassoni et al 2001;Ghe et al, 2002). Taken together, these findings suggest that during fasting ghrelin may act as a peripheral factor, pre-empting the increased metabolic demand induced by pregnancy and lactation, by inhibiting the development of preimplantation mouse embryos through its specific receptor (Kawamura et al, 2003). The involvement of ghrelin in embryo implantation has been demonstrated by its spatial-temporal expression (like that of its receptors) around the time of implantation .…”
Section: Ghrelin Pregnancy and Placental Physiologymentioning
confidence: 80%
“…Both ghrelin and GHSR mRNAs have been detected in the morula and in more advanced stages of embryo development (Kawamura et al, 2003). In addition, ghrelin protein is produced and secreted by the reproductive tract into uterine fluid (Kawamura et al, 2003) where its expression increases during fasting, as occurs in plasma (Gualillo et al, 2002). Ghrelin also negatively regulates cell viability and proliferation (Cassoni et al, 2000;Cassoni et al 2001;Ghe et al, 2002).…”
Section: Ghrelin Pregnancy and Placental Physiologymentioning
confidence: 99%
“…Its expression was also described in other areas of the CNS and in some peripheral tissues as: thyroid gland, pancreas, spleen, myocardium, adrenal glands [11,14,42,43], rat testis, ovary [44], human T lymphocytes [12], morula, blastocyts and embryos [13]. There were identified binding sites in the myocardium (highest binding capacity), adrenal gland, gonads, arteries, lung, liver, skeletal muscle, kidney, pituitary, thyroid gland, adipose tissue, veins, uterus, skin and lymph nodes [45].…”
Section: Ghrelin Receptorsmentioning
confidence: 93%
“…Ghrelin is also produced in the X/A cells of the intestine and in some others tissues such as the pancreas, kidney, placenta, lymphatics, *Address correspondence to this author at the Department of Physiology, Faculty of Medicine, Alameda Professor HernĂąni Monteiro, 4200-319 Porto, Portugal; Tel: +351 225513644; Fax: +351 225513646; E.mail: arsousa@med.up.pt # Both authors had the same contribution to the article gonads, adrenal, thyroid gland, heart, lung, pituitary, hypothalamus, eye [10], human B-and T-lymphocytes, neutrophils [1,[10][11][12], morula, blastocyts and embryos [13]. Ghelardoni observed that ghrelin gene expression and its protein were, in some tissues, dissociated [14].…”
Section: Ghrelinmentioning
confidence: 99%